2020
DOI: 10.3390/ijns6020044
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Effectiveness Study of Newborn Screening Methods for Four Lysosomal Storage Disorders

Abstract: Newborn screening for one or more lysosomal disorders has been implemented in several US states, Japan and Taiwan by multiplexed enzyme assays using either tandem mass spectrometry or digital microfluidics. Another multiplex assay making use of immunocapture technology has also been proposed. To investigate the potential variability in performance of these analytical approaches, we implemented three high-throughput screening assays for the simultaneous screening for four lysosomal disorders: Fabry disease, Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…In a previous Italian study, three of six positive males carried this variant [33], and a similar frequency was found in Austria where it was found in three of six positive males [26]. Moreover, more recently, a California NBS study also reported a high frequency of the p.Ala143Thr variant among positive newborns (22/50) [39]. This variant, previously associated with both classic [55] and later-onset phenotype [56], was subsequently considered benign [53,57].…”
Section: Interpretation Of Genetic Variantssupporting
confidence: 61%
“…In a previous Italian study, three of six positive males carried this variant [33], and a similar frequency was found in Austria where it was found in three of six positive males [26]. Moreover, more recently, a California NBS study also reported a high frequency of the p.Ala143Thr variant among positive newborns (22/50) [39]. This variant, previously associated with both classic [55] and later-onset phenotype [56], was subsequently considered benign [53,57].…”
Section: Interpretation Of Genetic Variantssupporting
confidence: 61%
“…Of these, one was confirmed as severe MPS I, 13 newborns had pseudo-deficiency alleles, three newborns had variants of unknown significance, and two had heterozygous pathogenic variants [ 27 ]. Other reports in a recent special issue: ‘CLIR applications for Newborn Screening’ in this journal confirm its value in significantly reducing referral rates [ 36 , 37 ]. Retrospective application of CLIR, at least, should be considered a useful exercise for programs screening for MPS I and other LSDs to determine whether initial screen positives could be reduced prior to second-tier testing.…”
Section: Prospective Screening Results From States Using Dmfmentioning
confidence: 74%
“… 39–46 Newborn screening programmes also have very low success rates for GD, so they do not appear to be cost-effective outside high-risk populations, with too many probands to identify a very small number of subjects, regardless of the used test (enzyme activity by microfluidics or mass spectrometry, combined with biomarkers or mass genetic analysis). 47 Newborn screening programs are also controversial because of the detection of potentially asymptomatic or oligosymptomatic cases or a high number of false positives, which may have ethical repercussions in terms of parental stress, overmedication or others. This type of search is more applicable in populations with a high prevalence of cases or in family studies.…”
Section: Discussionmentioning
confidence: 99%
“… 46 There is much controversy over the detection of false positives. 47 This approach is controversial because the incidence of cases in general population is low (~1/100,000 live births) in different populations and its application is only promoted in those communities with a high incidence of cases, such as in the Ashkenazi Jewish population, where the incidence is 1/850 births. Recently, the use of genetic analysis panels has been explored.…”
Section: Haematological Manifestations and Screening Programmesmentioning
confidence: 99%